2017
DOI: 10.1177/1039856217700298
|View full text |Cite
|
Sign up to set email alerts
|

Six years of national mental health seclusion data: the Australian experience

Abstract: Seclusion event rates in Australia's specialised public acute mental health hospital services are declining. The use of existing administrative data was instrumental in establishing a national data source to facilitate the monitoring and reporting of progress of seclusion reduction strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…A recent study reported variation in seclusion rates between Australian states and territories, as well as individual services (Allan et al . ). Studies that have examined seclusion rates in other countries suggest variation may be linked to the remoteness or size of inpatient units (Allan et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study reported variation in seclusion rates between Australian states and territories, as well as individual services (Allan et al . ). Studies that have examined seclusion rates in other countries suggest variation may be linked to the remoteness or size of inpatient units (Allan et al .…”
Section: Discussionmentioning
confidence: 97%
“…Studies that have examined seclusion rates in other countries suggest variation may be linked to the remoteness or size of inpatient units (Allan et al . ; Husum et al . ; Janssen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Despite overwhelming support for reducing and eliminating the use of seclusion and restraint, and the success of reduction programs, these practices continue to be used in mental health care (Allan et al . ; Bowers et al . ; Bullock et al .…”
Section: Introductionmentioning
confidence: 99%
“…Despite overwhelming support for reducing and eliminating the use of seclusion and restraint, and the success of reduction programs, these practices continue to be used in mental health care (Allan et al 2017;Bowers et al 2017;Bullock et al 2014;Gerace et al 2014;Muir-Cochrane et al 2014;Oster et al 2016;Te Pou o te Whakaaro Nui, 2017). Mental health nurses play a central role in the provision of mental health care and as such represent the staff that are most likely to use seclusion and restraint (NMHCCF, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The use of seclusion, mechanical, and physical restraint has been extensively researched in Australia and internationally (Allan et al . ; Beghi et al . ; Cowman et al .…”
Section: Introductionmentioning
confidence: 99%